THE HYPERREALITY OF THE CHARACTER KATRINA IN THE NOVEL “ALL YOU NEED IS LOVE” BASED ON JEAN BAUDRILLARD PERSPECTIVE - Masadi, M Anwar; Chilwina, Nadhita (Annual International Conferences on Language, Literature, and Media, 2023)
This research discusses and exposes the fantasy images in the novel “All You Need is Love," which will be revealed using Jean Baudrillard's Postmodernism theory. This novel is a young adult genre that discusses the problems of love, family, and fantasy that are made to seem real. Fantasy is a part of hyperreality that occurs because of simulation. Hyperreality is part of the discussion of postmodern theory, which discusses the state of society in the postmodern era. Postmodernism is an era in which technological and scientific developments occur. This research is a type of qualitative research that produces data and descriptive analysis. The material object in this study is the novel "All You Need is Love" by Fakhrisina Amalia, published by Gramedia Pustaka in 2015, while the formal object is data in the form of paragraphs. These discourse texts contain hyperreality following Jean Baudrillard's concept of Postmodernism. This study found six hyperreality images: 1. Aiden seems like Prince Charming from a fairy tale, 2. Long distance relationship is bullshit, 3. Brigadoon: Part of heaven that fell to earth, 4. Descendants of the legendary city residents, 5. A Complicated Love, and 6. Without love, there is nothing left to do.